Associations of inflammatory cytokines with palmoplantar pustulosis: a bidirectional Mendelian randomization study - Liu, Chengling; Liu, Xingchen; Xin, Haiming; Li, Xin (Frontiers in Medicine, 2024)
Background: Variations in circulatory cytokine levels have been noticed during the onset and course of palmoplantar pustulosis (PPP); however, whether these changes are due to etiologic or secondary factors is unclear. To clarify the causal link between the two, we conducted a summarized-level bidirectional Mendelian randomization (MR) analysis in this study.Methods: A FinnGenbiobank GWAS of 212,766 people (524 PPP patients, 212,242 controls) provided summary data for the PPP, whereas genetic instrumental variables (IVs) linked to circulation cytokine levels were gathered from a genome-wide association study (GWAS) of 14,824 European individuals. The inverse variance weighted (IVW) method, weighted median (WME), simple model, and MR-Egger were employed to ascertain the changes in PPP pathogenic cytokine taxa. Sensitivity analysis, which included horizontal pleiotropy analysis, was then conducted. The reliability of the results was assessed using the leave-one-out approach and the MR Steiger test, which assessed the strength of a causal relationship. In order to evaluate the reverse causality between PPP and circulating cytokine levels, a reverse MR analysis was carried out.Our study demonstrated positive associations between C-X-C motif chemokine 6 (CXCL6) with PPP (odds ratio, OR 1.257, 95%CI: 1.001-1.570, p= 0.043).C-C motif chemokine 19 (CCL19) and Interleukin-6 (IL-6) were suggested to be protectively associated with the development of PPP (OR: 0.698,95% CI: 0.516-0.944, p=0.020; OR: 0.656, 95%CI:0.437-0.985, p=0.042). Results were steady after sensitivity and heterogeneity analysis.At the genetic prediction level, we identified causally connected inflammation-related variables that contributed to the onset and development of PPP.The therapeutic options for some refractory PPP have expanded thanks to tailored cytokine therapy, which has also generated fresh concepts for PPP diagnostics and mechanism investigation.